ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN KOBER MIE SETAN DI SURABAYA - Effendy, Achmad; Putriyana, Annisa (JEM17: Jurnal Ekonomi Manajemen, 2016)
The problems of this study are partial and simultaneous Is factors of service quality dimensions that include tangibles, reliability, responsiveness, assurance and empathy have a significant influence on consumer satisfaction at Kober Noodle Eating Satan in Surabaya? And which variables are the most dominant influence on consumer satisfaction at Kober Noodle Eating Satan in Surabaya? Based on the research results, obtained the following regression equation: Y = 4.170 + 0.249 + 0.008 X1 + 0.346 X2 + 0,115 X3 X5 + X4 + 0.123 EThe results showed that there was a significant effect of the variable quality of services that include tangibles, reliability, responsiveness, assurance, and empathy towards customer satisfaction, it is proved by the test value F where significant value of 0.000. The research result t test showed there are three variables were not significant and the other two significant. Of the acquisition value equation of multiple linear regression model all variables showed a positive coefficient that shows the influence of service quality to customer satisfaction. Keofisien of determination of 0.377, which means that 37.7% variable tangibles, reliability, responsiveness, assurance, and empathy affect customer satisfaction, while 62.3% is influenced by other variables not studied like promotions and product quality. Based on the results of the Multiple Correlation Coefficient unknown value R of 0.614, indicating that the proportion of the relationship between tangibles, reliability, responsiveness, assurance, and empathy to customer satisfaction is very strong and positive at 61.4% and the remaining 38.6% influenced by unobserved variables the results showed that the variable responsiveness is the dominant variable with a beta value of 0.344.Keywords: tangible, reliability, responsiveness, assurance, empathy, customer satisfaction.